The rationale for and long-term outcome of incomplete axillary staging in elderly women with primary breast cancer. Issue 11 (November 2018) - Poodt, Ingrid G.M.; Schipper, Robert-Jan; Vugts, Guusje; Woensdregt, Karlijn; van der Sangen, Maurice; Voogd, Adri C.; Nieuwenhuijzen, Grard A.P.
Abstract: Background: The proportion of elderly women diagnosed with breast cancer is rising. Standard treatment, including axillary staging, is often not given to these patients. This study aimed to investigate reasons to omit any surgical axillary staging or to refrain from completion axillary lymph node dissection (cALND) after positive-sentinel lymph node biopsy (SLNB); so-called "incomplete staging". Furthermore, the impact of incomplete staging on regional control and survival in patients aged 75 or older was evaluated. Methods: A retrospective cohort study was conducted including all primary breast cancer patients aged 75 or older, diagnosed between 2001 and 2008, and documented by the Netherlands Cancer Registry (NCR). Patients with incomplete staging were compared to patients with complete axillary staging. Survival analyses were used to determine the risk of local, regional and distant recurrence and overall survival. Results: In total, 1467 of 2116 (69%) patients were considered eligible, of whom 258 (17.2%) had incomplete axillary staging. For 93 patients, diagnosed in 6 of the 10 hospitals in the NCR-area, examination of clinical records revealed that age, comorbidities and patient preferences were the main reason for omitting complete axillary staging. The 10-year axillary recurrence rate in these 93 patients was 5.2% (95% CI, 0.03–10.1). Of the 77 patients who had died, 64 (83%) died of non-breast-cancer-related causes. No significant difference in overall survival was observed between patients with or without complete axillary staging. Conclusion: This study demonstrates that the omission of complete axillary staging is common in selected elderly breast cancer patients with ≥2 comorbidities, with no apparent impact on regional control and 10-year overall survival.